Exploring the Pedagogical Effectiveness of Clickers - Robin K. Morgan (Park University, 2008)
Clickers, electronic response systems, are widely popular in college classrooms and proponents have argued clickers can increase student engagement, active learning, and, perhaps most importantly, student comprehension. Determining whether the effectiveness of clickers justified their purchase seemed warranted. A campus-wide project was developed to address this questions. Five university instructors adopted clickers in one of their introductory courses (psychology, speech, accounting, and education) while teaching a second, control course. Contrary to expectation, attrition was higher and grades were lower in the clicker courses, although these differences were not statistically significant.